Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/ph14070676
|View full text |Cite
|
Sign up to set email alerts
|

Phytomedicines Targeting Cancer Stem Cells: Therapeutic Opportunities and Prospects for Pharmaceutical Development

Abstract: The presence of small subpopulations of cells within tumor cells are known as cancer stem cells (CSCs). These cells have been the reason for metastasis, resistance with chemotherapy or radiotherapy, and tumor relapse in several types of cancers. CSCs underwent to epithelial–mesenchymal transition (EMT) and resulted in the development of aggressive tumors. CSCs have potential to modulate numerous signaling pathways including Wnt, Hh, and Notch, therefore increasing the stem-like characteristics of cancer cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 83 publications
0
9
0
Order By: Relevance
“…Quercetin reduces the migration, invasion, and tumorsphere formation of prostate CSCs, whereas apigenin inhibits the growth and metastatic potential of glioblastoma stem cells by blocking c-MET signaling [ 23 , 43 ]. Furthermore, plant extracts containing various functional ingredients have also exhibited potential anti-CSC effects [ 20 , 21 , 22 , 23 , 24 , 44 ]. Chloroform extracts from Sparassis crispa, Citrus unshiu Markovich, and Portulaca oleracea have been found to inhibit the self-renewal capabilities of cervical CSCs or glioblastoma stem cells through apoptosis induction and the suppression of stemness markers [ 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin reduces the migration, invasion, and tumorsphere formation of prostate CSCs, whereas apigenin inhibits the growth and metastatic potential of glioblastoma stem cells by blocking c-MET signaling [ 23 , 43 ]. Furthermore, plant extracts containing various functional ingredients have also exhibited potential anti-CSC effects [ 20 , 21 , 22 , 23 , 24 , 44 ]. Chloroform extracts from Sparassis crispa, Citrus unshiu Markovich, and Portulaca oleracea have been found to inhibit the self-renewal capabilities of cervical CSCs or glioblastoma stem cells through apoptosis induction and the suppression of stemness markers [ 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that there can be different subpopulations of CSCs within the tumor mass identified by cancer stem cell surface markers on normal stem cells with similar characteristics as normal stem cells, such as self-renewal and multilineage differentiation capabilities, with a much higher half-life than that of most other cells [32]. The intrinsic properties of self-renewal, multipotency, and longevity render stem cells more susceptible to accumulating gene mutations leading to neoplastic transformation, as proposed by the cancer stem cell hypothesis [33,34]. They have been found to be the key driver of tumorigenicity, tumor heterogeneity, recurrence, and drug resistance in many cancer types, and different targeted molecules, including nanoparticles-based drug delivery systems, are being tested for effectively targeting CSC related pathways for cancer treatment [35,36,37.38].…”
Section: Molecular Basis Of Cellular Reprogramming and Cancer Therapymentioning
confidence: 99%
“…Furthermore, phytochemicals combined with chemotherapeutic agents target multiple signal cascades to chemosensitize cancer cells to drugs, representing a novel and potentially effective therapeutic strategy. ,, Phytochemicals have been shown to suppress cancer by modulating various signal transduction pathways and employing the anticancer effect by promoting cellular apoptosis, cell proliferation, and inhibiting self-renewal pathways that are responsible for CSC survival (Figure ). , However, to improve the limitations and translational success of phytochemicals, researchers have focused their efforts on developing phytochemical-based nanoformulations or phytonanomedicine for specific tumor targeting abilities with minimal off-target effects for better therapeutic outcomes. ,,, Therefore, nanomedicine strategies are mainly employed to enhance the therapeutic index by inhibiting cancer survival signals and modulating TME.…”
Section: Opportunities For Phytonanomedicine In Cancer Therapymentioning
confidence: 99%